The Readiness of Elementary School Teacher to Teach English: The Merdeka Curriculum Perspectives - Rojuna, Citra Arba; Tahir, Muh.; G, Hasriani (Journal of Excellence in English Language Education, 2024)
This research aims to find out the readiness of elementary school teacher to teach English since Merdeka curriculum has been implemented. The method used in this research is a qualitative descriptive method. The participant in this research were teachers from SDN. No 57 Centre Mangadu who assigned to teach English since Merdeka curriculum has been implemented in elementary school. A teacher was selected as participant by using purposive sampling technique. The instruments used in this research were interview to analyze the data qualitatively and descriptively from the interview transcript and also an observation by using observation checklist to check the consistency between the results of interview and observation. Overall, there are readiness and unreadiness of the teacher to teach English in elementary school since Merdeka curriculum has been implemented. The readiness regarding the teacher in teaching English include 1) the teacher makes thorough preparations before the English teaching and learning process in class, 2) the teacher prepares herself independently to teach English, 3) the teacher studies materials to be taught before the teaching and learning process, 4) the school provides sufficient facilities for learning English, and 5) the teacher experiences difficulties in teaching English but are able to overcome them in various ways, 6) the teacher uses discussion and project methods in learning English carried out by students in groups, and 7) implement inclusive learning in accordance with the Merdeka curriculum policy. Meanwhile, the unreadiness of teacher in teaching English include 1) the teacher assigned to teach English is graduate from primary school teacher education, not English education, 2) the teacher admitted that she did not know a lot of vocabulary and grammar in English and how to pronounce the words correctly, 3) there is no training carried out by the school for teachers assigned to teach English, 4) the teacher only use internet as a medium for learning English, and 5) the Merdeka curriculum is not applied in all classes, 6) mispronunciation comes from the teacher in English learning and teaching process in the class. From these findings, it can be concluded that the teacher is ready to teach English in elementary school as she assigned to because the readiness of the teacher is more dominant than her unreadiness to teach English.